2019
DOI: 10.1039/c9mt00051h
|View full text |Cite
|
Sign up to set email alerts
|

First-in-class ruthenium anticancer drug (KP1339/IT-139) induces an immunogenic cell death signature in colorectal spheroids in vitro

Abstract: The ruthenium complex sodium trans-[tetrachloridobis(1H-indazole)ruthenate(III)] (KP1339/IT-139) showed preclinical activity in a variety of in vivo tumor models including a highly predictive colon cancer model. The compound has entered clinical trials, where patients experienced disease stabilization accompanied by mild side effects.KP1339, a GRP78 inhibitor, disrupts endoplasmic reticulum (ER) homeostasis leading to cell death. The PERK/eIF2a-branch of the ER plays an essential role in the cascade of events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 42 publications
1
99
0
2
Order By: Relevance
“…In this work, we could individuate the impact on biochemical pathways related to redox stress: glutathione metabolism (glutathione, oxidized glutathione and NADP+ are up-, glutamate down-regulated), purine metabolism, pentose phosphate pathway (ribulose 5-phosphate/ribose 5-phosphate down-regulated), which could be explained by the hypothesized reduction of the drug. Redox stress and elevation of ROS protective proteins [42,50] were confirmed by previous proteomics studies. Finally, pathways such as glycerophospholipid metabolism (strong choline down-regulation) and various amino acid metabolism-related pathways were pinpointed (glutamine and glutamate metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In this work, we could individuate the impact on biochemical pathways related to redox stress: glutathione metabolism (glutathione, oxidized glutathione and NADP+ are up-, glutamate down-regulated), purine metabolism, pentose phosphate pathway (ribulose 5-phosphate/ribose 5-phosphate down-regulated), which could be explained by the hypothesized reduction of the drug. Redox stress and elevation of ROS protective proteins [42,50] were confirmed by previous proteomics studies. Finally, pathways such as glycerophospholipid metabolism (strong choline down-regulation) and various amino acid metabolism-related pathways were pinpointed (glutamine and glutamate metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis).…”
Section: Discussionsupporting
confidence: 71%
“…There are indications that this drug is a GRP78 inhibitor, an ER stress sensing chaperone [39,49]. It not only induces ER stress and unfolded protein response, but it has also been shown that it exhibits the hallmarks of immunogenic cell death, calreticulin exposure, and ATP secretion among others [42]. Less is known about the metabolic effects of this compound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BOLD-100 is a novel small molecule that showed modest anti-tumor activity in a Phase I clinical trial [12]. Mechanistically, BOLD-100 has been shown to down-regulate GRP78 in thapsigargin-mediated stressed cancer cells [15] and trigger immunogenic cell death through the PERK/EIF2a branch of the UPR accompanied by ROS production, release of high mobility group box 1 (HMGB1) and ATP secretion via autophagy [31]. Sensitivity toBOLD-100 can vary in different cells and cellular responses including cell cycle (via G2 cell cycle arrest), DNA repair pathway, and cellular metabolism are known to be affected [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib is a specific inhibitor of the 26S proteasome subunit and induces apoptosis of various cancer cells, associated with enhanced phagocytosis and DC cross‐presentation of tumor antigens to T cells 116 . In preclinical CRC models, bortezomib, HSP inhibitors, mTOR/PI3K inhibitors, BET inhibitors or a GRP78 inhibitor induced ER stress‐associated cell death 85‐90 . Interestingly, several drug combinations were particularly effective in killing CRCs harboring mutant KRAS/BRAF or SPOP through elevated ER stress and DR5 expression 91,92 .…”
Section: Icd‐inducing Agents In Crc Prevention and Therapymentioning
confidence: 99%